Anterolateral Ligament Reconstruction Does Not Delay Functional Recovery, Rehabilitation, and Return to Sport After Anterior Cruciate Ligament Reconstruction: A Matched-Pair Analysis From the SANTI (Scientific ACL Network International) Study Group - Marine Coquard, M.D; Alessandro Carrozzo, M.D; Adnan Saithna, M.D; Gregory Vigne, Ph.D; Meven Le Guen; Yann Fournier, M.D; Jean-Philippe Hager, M.D; Thais Dutra Vieira, M.D; Bertrand Sonnery-Cottet, M.D (Elsevier, 2022)
Purpose: To determine whether the addition of an anterolateral ligament reconstruction (ALLR) resulted in delayed functional recovery (based on the Knee Santy Athletic Return to Sport [K-STARTS] score) at 6 months after anterior cruciate ligament reconstruction (ACLR). Methods: A retrospective analysis of prospectively collected data from consecutive patients who underwent an ACLR between September 2017 and December 2020 was conducted. Patients who received an isolated hamstring autograft (isolated ACLR group) were propensity matched in a 1:1 ratio to patients who received a hamstring autograft ACLR combined with an ALLR (ACLR-ALLR group). Outcome measures included the Tegner Activity Scale and the K-STARTS test-a validated composite return-to-sports test (including the Anterior Cruciate Ligament-Return to Sport After Injury scale, Qualitative Assessment of Single-Leg Landing tool, limb symmetry index, and ability to change direction using the Modified Illinois Change of Direction Test). Results: The study included 111 matched pairs. At 6 months postoperatively, there were no significant differences between groups in the overall K-STARTS score (65.4 for isolated ACLR vs 61.2 for ACLR-ALLR, P = .087) or the Tegner Activity Scale score (3.7 for isolated ACLR vs 3.8 for ACLR-ALLR, P = .45). In addition, an evaluation of the subscales of the K-STARTS score revealed no disadvantage across the domains of neuromuscular control, limb symmetry index, agility, or psychological readiness to return to sport when an ALLR was performed. Conclusions: The addition of ALLR at the time of ACLR does not delay functional recovery. Specifically, at 6 months postoperatively, there was no disadvantage in patients undergoing ALLR-ACLR, when compared with those undergoing isolated ACLR, with respect to neuromuscular control, limb symmetry indices (hop tests), agility, or psychological readiness to return to sport. Level of Evidence: Level III, retrospective comparative study.